Preferensi Metode Mengajar Dosen terhadap Sikap, Motivasi dan Minat Berwirausaha Mahasiswa Akuntansi Universitas Prima Indonesia - Tina Novianti Sitanggang; Faathir Nurul Yasiin (Politeknik Ganesha Medan, 2021)
This study aims to analyze the effect of lecturer teaching methods on the Attitudes, Motivation, and Entrepreneurial Interests of Accounting Students at Prima Indonesia University. This study uses primary data, namely by distributing questionnaires to 2015/2016 accounting students who have taken entrepreneurship courses with a sample of 236 students taken using the Slovin formula. This study was analyzed using SPSS. The result of the research is that simultaneously from the third variable independent of the dependent variable Y (Entrepreneurial Interest) is 0.549 x 100% = 54.9%. In other words, 54.9% of Entrepreneurial Interest can be expressed by the 3 independent variables (Entrepreneurial Knowledge, Attitudes, and Motivation). Partially the 3 independent variables have a significant positive effect on Entrepreneurial Interest. The lecturer teaching method is proven as a variable that has a significant effect on the relationship between the independent variables and the dependent variable.